ASEAN HUMAN RIGHTS CHALLENGES: TOWARDS A REGIONAL-BASED SOUTHEAST ASIAN COURT OF HUMAN RIGHTS - Bagus Ananda Pratama, I Gede; Budi Arsika, I Made (Kertha Negara : Journal Ilmu Hukum; Vol. 02, No. 02, Februari 2014)
As the declaration of ASEAN Human Rights Declaration, ASEAN had enabled new options in its framework of human rights settlement issues in its region. Such momentum shall be considered as an entry point in transforming long-standing values of consultative and consensual of ASEAN in dealing with human rights issues in ASEAN. Such aforementioned values had been assessed their relevance in handling ASEAN human rights violations which had been unresolved. The application of regional-based institution by several other regions might be considered as a blueprint for ASEAN court of human rights in the future.
Keywords: ASEAN, Human Rights, Regional, Court